Design UI/UX e-commerce photography services using the Lean User Experience Model and System Usability Scale (SUS) Assessment - Kurniawan Zaini; Tri Marlianti; Maryani Maryani (Jurnal Nasional Ilmu Komputer, 2023)
Studio Citarasa Fotography (SCF) is a photographer business that has been operating for 5 years since 2017 with a total of 87 customers. This number of consumers according to interviews with the studio owners is very small because the studio has not stopped promoting both inside and outside the city. The objective of this research is to design the UI/UX e-commerce Photography Services website in the Citarasa Photography studio and implement the Lean UX Model based on simple and responsive design, understanding user wishes and needs, informative, interactive, complete, sustainable, and personalized. Research results based on the test scenario respondents/participants successfully completed all UI/UX tasks for e-commerce photography services without significant restrictions, but in the scenario there is little information provided about the possibility of making changes for iterations to become more responsive in which the screen can be adjusted to an android or tablet screen. In addition, the test results obtained using the System Usability Scale (SUS) were achieved with an average score of 89.25. It can be said that the score is in the best imaginable category with a scale of A. This means that based on usability, the data obtains a judgment that is acceptable or acceptable.